2016
DOI: 10.1016/j.nano.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of malaria infected red blood cells by surface enhanced Raman spectroscopy

Abstract: Surface enhanced Raman spectra (SERS) of normal red blood cells (RBCs) and Plasmodium falciparum infected RBCs (iRBCs) at different post invasion time were obtained based on silver nanorod array substrates. Distinct spectral differences were observed due to the cell membrane modification of RBCs during malaria infection. The SERS spectra of ring stage iRBCs had a characteristic Raman peak at Δν = 1599 cm−1 as compared to those of normal RBCs, while the trophozoite and schizoid stages had identical SERS spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 42 publications
(56 reference statements)
0
38
0
Order By: Relevance
“…Compared with the mean spectra of untreated osteosarcoma cell, both DAPT-treated groups showed a decrease in the spectral features at 787 cm -1 (uracil, thymine, and cytosine, DNA backbone O-P-O stretching) [27,28], 840 cm -1 (carbohydrate, glucose) [29], 1320 cm -1 (protein, C-H) [30,31], 1656 cm -1 (protein, amide I, α-spiral) [19,32] and 2934 cm -1 (lipid, CH 3 ) [27], associated with nucleic acid, protein, lipid, and carbohydrate content. In both 10T and 20T groups, a decrease in peak intensity, as compared to the UT group, was observed at 787 cm -1 , which is associated with uracil, thymine, and cytosine ring breathing modes in DNA and RNA bases.…”
Section: Ch3mentioning
confidence: 79%
“…Compared with the mean spectra of untreated osteosarcoma cell, both DAPT-treated groups showed a decrease in the spectral features at 787 cm -1 (uracil, thymine, and cytosine, DNA backbone O-P-O stretching) [27,28], 840 cm -1 (carbohydrate, glucose) [29], 1320 cm -1 (protein, C-H) [30,31], 1656 cm -1 (protein, amide I, α-spiral) [19,32] and 2934 cm -1 (lipid, CH 3 ) [27], associated with nucleic acid, protein, lipid, and carbohydrate content. In both 10T and 20T groups, a decrease in peak intensity, as compared to the UT group, was observed at 787 cm -1 , which is associated with uracil, thymine, and cytosine ring breathing modes in DNA and RNA bases.…”
Section: Ch3mentioning
confidence: 79%
“…AgNR array substrates were fabricated by the OAD method in a custom‐built e‐beam deposition system (DE500, DE Technology Inc., Beijing, China). Detailed characterization of the enhancement factor, uniformity, and repeatability of the substrates has been reported previously . Briefly, glass slides were cut into 1 × 1 cm 2 square pieces and were sonicated in ethanol for 10 min, dried by high purity nitrogen.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Changes in the red blood cells (RBC) have been traditionally used to detect mosquito-borne infection, and it has also been found that some of the molecular changes in RBC can also be detected using SERS to potentially achieve high diagnostic sensitivities. Zhao's group at the University of Georgia used the SERS spectral features apparent in RBC infected with Plasmodium falciparum (iRBC) to differentiate varying stages of the parasite in the blood as iRBC at different post-invasion times exhibit different cell membrane modifications [104]. In this study, they analyzed and compared the intrinsic spectral signatures of healthy RBC and iRBC on silver nanorod array substrates.…”
Section: Metabolites As Biomarkersmentioning
confidence: 99%